Effects of 8 wk of 16:8 time-restricted eating in male middle- and long-distance runners - Brady, A. J.; Langton, H. M.; Mulligan, M.; Egan, B. (Medicine & Science in Sports & Exercise, 2021)
Purpose: Eight weeks of time-restricted eating (TRE) in concert with habitual exercise training was investigated for effects on body composition, energy and macronutrient intakes, indices of endurance running performance, and markers of metabolic health in endurance athletes. Methods: Male middle- and long-distance runners (n = 23) were randomly assigned to TRE (n = 12) or habitual dietary intake (CON; n = 11). TRE required participants to consume all of their dietary intake within an 8-h eating window (so-called 16:8 TRE), but dietary patterns, food choices, and energy intake were ad libitum during this window. Participants continued their habitual training during the intervention period. Participants completed an incremental exercise test before (PRE) and after (POST) the 8-wk intervention for the assessment of blood lactate concentrations, running economy, and maximal oxygen uptake. Fasted blood samples were analyzed for glucose, insulin, and triglyceride concentrations. Dietary intake was assessed at PRE, MID (week 4), and POST using a 4-d semiweighed food diary. Results: Seventeen participants (TRE, n = 10; CON, n = 7) completed the intervention. Training load did not differ between groups for the duration of the intervention period. TRE resulted in a reduction in body mass (mean difference of -1.92 kg, 95% confidence interval = -3.52 to -0.32, P = 0.022). Self-reported daily energy intake was lower in TRE at MID and POST (group-time interaction, P = 0.049). No effect of TRE was observed for oxygen consumption, respiratory exchange ratio, running economy, blood lactate concentrations, or heart rate during exercise, nor were there any effects on glucose, insulin, or triglyceride concentrations observed. Conclusion: Eight weeks of 16:8 TRE in middle- and long-distance runners resulted in a decrease in body mass commensurate with a reduction in daily energy intake, but it did not alter indices of endurance running performance or metabolic health.